Integrated experimental and computational fluid dynamics study of graphene nanoplatelet-based nanofluids modified with surfactants in photovoltaic-thermal heat exchangers - Puspitasari, Poppy; Anwar, Saiful; Pramono, Diki Dwi; Permanasari, Avita Ayu; Zakaria, Yahya; Mohd Rosli, Mohd Afzanizam (Oxford University Press, 2025)
This study investigates the effects of graphene nanoplatelet-based nanofluids, modified with various surfactant types and concentrations, on the thermal performance of solar thermal systems. The nanofluids were synthesized and characterized in terms of structural, thermophysical, rheological, and dispersion properties. These data were integrated into computational simulations of a photovoltaic-thermal heat exchanger. Among all formulations, the nanofluid containing 0.1 wt% polyvinylpyrrolidone exhibited the highest thermal efficiency, increasing from 40.21% (water) to 45.26%. This enhancement is attributed to its superior thermal conductivity, higher specific heat capacity, low viscosity at elevated shear rates, and stable dispersion. Rheological testing confirmed shear-thinning, non-Newtonian behavior that facilitates convective heat transfer. In contrast, nanofluids without surfactants or with anionic surfactants showed higher viscosity and reduced stability, resulting in lower thermal efficiency. The integrated experimental computational approach offers a comprehensive understanding of the mechanisms governing nanofluid-enhanced heat transfer in photovoltaic-thermal systems. Enhancing the heat exchanger directly improves overall system performance. The proposed nanofluid formulation presents a viable pathway toward scalable, efficient solar thermal applications. Future work should focus on long-term stability and techno-economic validation under real-world operating conditions.